1977
DOI: 10.1007/bf00273255
|View full text |Cite
|
Sign up to set email alerts
|

DIPI and DAPI: Fluorescence banding with only negligible fading

Abstract: DIPI and DAPI produce distinct fluorescent bands in human chromosomes similar to quinacrine banding patterns. Additionally, the AT rich secondary constrictions in the chromosomes Nos. 1, 9 and 16 are brightly fluorescent. On the other hand the brilliantly fluorescent regions after staining with quinacrine mustard in the chromosomes Nos. 3 and 4, satellites and some other regions in the acrocentric chromosomes are less striking. The distal part of the Y, however, is clearly discernible. Thus DIPI and DAPI seem … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
19
0
3

Year Published

1979
1979
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(22 citation statements)
references
References 21 publications
0
19
0
3
Order By: Relevance
“…This heterogeneity has been attributed to the complex nature of highly repetitive DNA in sarcophagids which may be responsible for differences in underlying DNA sequences (Hershfield and Swift 1990). DAPI belongs to the group of fluorochromes which specifically binds to AT-base pairs (Lin et al 1977, Schnedl et al 1977. Thus, the brightly fluorescent bands with DAPI in the mitotic complement of Boettcherisca species represent AT-rich DNA sequences of the heterochromatin.…”
Section: Discussionmentioning
confidence: 99%
“…This heterogeneity has been attributed to the complex nature of highly repetitive DNA in sarcophagids which may be responsible for differences in underlying DNA sequences (Hershfield and Swift 1990). DAPI belongs to the group of fluorochromes which specifically binds to AT-base pairs (Lin et al 1977, Schnedl et al 1977. Thus, the brightly fluorescent bands with DAPI in the mitotic complement of Boettcherisca species represent AT-rich DNA sequences of the heterochromatin.…”
Section: Discussionmentioning
confidence: 99%
“…Interphase ceils were fixed with 3% glutaraldehyde for 10 rain and five subsequent changes of 2% perchloric acid. Mitotic cells were blocked by addition of 1 gg/ml colchicine for three hours.-Chromosome preparations were performed in situ as previously described (Zorn et al 1979) and stained with DAPI (Schnedl et al 1977). Autoradiography was carried out following standard procedures and autoradiographs were slightly stained with acetic orceine (Zorn et al 1979).…”
Section: Posttreatment Of Microirradiated Cellsmentioning
confidence: 99%
“…It has in fact been demonstrated that all fluorescent stains bind to DNA and, if classified on the basis of their binding specificity for DNA bases, they can be divided into two groups: those with specific bonds for the A-T bases, such as H 33258, DAPI, DIPI and 2,7-di-t-butylproflavine (WEISBLUM and HAENSSLER 1974;LIN et al 1977;ScHNEDL et al 1977;MuLLER et al 197 3) (unlike quinacrine and daunomycin which have a low binding specificity and fluoresce mainly in the presence of A-T bases (SUMNER 1981;LIN and VAN DE SANDE 1975) and those which are specifically bound to G-C such as chromomicyn AJ, mithramycin and olivomycin ( VAN DE SANDE et al 1977). In many organisms these fluorochromes stain only the heterochromatin.…”
mentioning
confidence: 99%
“…All the available data show that there is a more satisfactory correlation between A-T richness and degree of fluorescence of the chromosomal areas with Hoechst than with quinacrine. DAPI, DIPI, 2,7-di-t-butylproflavine, which like H33258 belong to the group of fluorochromes with binding affinity for A-T DNA bases, produce on the human chromosomes a fluorescence pattern like that of H33258, but with a difference in the intensity of fluorescence in the different areas, in particular the heterochromatin of chromosomes 9 and Y are scarcely fluorescent (SCHNEDL et al 1977;DISTECHE and BoNTEMPS 1974).…”
mentioning
confidence: 99%